PS-BPP06-7: ASSOCIATION BETWEEN SALT INTAKE AND BLOOD PRESSURE IN COMMUNITY-DWELLING OLDER PEOPLE: THE SONIC STUDY. (January 2023) - Yoshida, Hiroko; Kabayama, Mai; Godai, Kayo; Akasaka, ken; Yamamoto, Kouichi; Ikebe, Kazunori; Yasumoto, Saori; Gondo, Yasuyuki; Rakugi, Hiromi; Kamide, Kei
Abstract : Objective: It is well known that excessive salt intake is associated with hypertension (HT) and salt intake reduction lowers blood pressure. However, the knowledge of salt intake and blood pressure in the older people is not sufficient. This study aimed to clarify the relationship between salt intake and blood pressure among community-dwelling Japanese older people. Design and method: This study was cross-sectional design based on a prospective cohort study called the SONIC (Septuagenarians, Octogenarians and Nonagenarians Investigation with Centenarians) study. We used data collected from 2010 to 2012. The dependent variable was the blood pressure at the venue and the independent variable was salt intake. Salt intake was calculated using the brief-type self-administered diet history questionnaire (BDHQ). After adjustment for energy using the residual method, Salt intake was classified into quartiles. Blood pressure values for each quartile were compared by Jonckheere-Terpstra test. Results: The number of participants was 2, 163 (female: 53.3%). Persons who may have over- or under-reporting nutrition and had no blood pressure data was excluded. Participants of 70 ± 1 years old were 947 (HT: 50.2%), 80 ± 1 years old were 951 (HT: 63.9%), 90 ± 1 years old were 265 (HT: 50.6%). There was no clear difference of systolic blood pressure among the four quartiles of salt intake. Participants taking angiotensin II receptor blocker (ARB) were 448, and mean systolic blood pressure in the four quartiles of salt intake were Q1:142.1 ± 17.7mmHg, Q2: 145.2 ± 17.3, Q3: 146.1 ± 17.2, and Q4: 147.8 ± 18.8. There was a stepwise increase in systolic blood pressure with increasing salt intake quartile (p = 0.018 for trend). Conclusions: For the elderly taking ARBs, salt reduction was shown to improve blood pressure control, but for the other elderly, no effect of salt intake was observed. Further studies are needed to examine including other factors what affects blood pressure for older population.